Sürdürülebilir Kalkınma Hedefleri Bağlamında Kadın Akademisyenlerin Yaşam Boyu Öğrenme Deneyimleri - Kuloğlu, Ayşenur; Orhan, Fulya Görkem; Özer, Merve (Fırat University, 2026)
This study aims to examine the lifelong learning experiences of female academics within the framework of the Sustainable Development Goals (SDGs). Designed based on a qualitative research method, the study adopts a phenomenological design. The sample of the research consists of 13 female academics working at Fırat University during the 2024–2025 academic year, selected through criterion sampling. Data were collected through a semi-structured interview form. Content analysis was used to analyze the data. The findings revealed that female academics consider lifelong learning meaningful in terms of personal development, social contribution, and professional responsibility. Participants stated that the SDGs, particularly in the context of gender equality, environmental awareness, and quality education, increased their motivation to learn. Institutional support through education, projects, and training opportunities was found to strengthen this process. It was also observed that female academics contributed to their environments as role models. To enhance the effectiveness of these experiences in the future, it is recommended that they be supported through flexible working hours, hybrid models, and gender equality policies. In addition, the training programs offered should support lifelong learning. This study specifically addresses the relationship between lifelong learning and sustainable development in the context of female academics.

Bu araştırma, Sürdürülebilir Kalkınma Hedefleri (SKH) çerçevesinde kadın akademisyenlerin yaşam boyu öğrenme deneyimlerini incelemeyi amaçlamaktadır. Nitel araştırma yöntemine dayalı olarak desenlenen çalışma, olgubilim (fenomenoloji) desenine sahiptir. Araştırmanın örneklemi, ölçüt örnekleme yöntemiyle seçilen ve 2024–2025 eğitim-öğretim yılında Fırat Üniversitesi’nde görev yapan 13 kadın akademisyenden oluşmaktadır. Veriler, yarı yapılandırılmış görüşme formu aracılığıyla toplanmıştır. Verilerin analizinde içerik analizi yöntemi kullanılmıştır. Bulgular, kadın akademisyenlerin yaşam boyu öğrenmeyi kişisel gelişim, toplumsal katkı ve mesleki sorumluluk açısından anlamlı bulduklarını ortaya koymuştur. Katılımcılar, sürdürülebilir kalkınma hedeflerinin özellikle toplumsal cinsiyet eşitliği, çevresel duyarlılık ve nitelikli eğitim bağlamında öğrenme motivasyonlarını artırdığını ifade etmişlerdir. Kurumların sunduğu eğitim, proje, eğitime olan desteklerin bu süreci güçlendirdiği belirlenmiştir. Kadın akademisyenlerin çevrelerine rol model olarak katkı sundukları görülmüştür. Gelecekte bu deneyimlerin daha etkili hale gelmesi için esnek çalışma saatleri, hibrit modeller ve toplumsal cinsiyet eşitliği politikalarıyla desteklenmesi önerilmektedir. Ayrıca sunulan eğitimler yaşam boyu öğrenmeyi destekler nitelikte olmalıdır. Çalışma, yaşam boyu öğrenmenin sürdürülebilir kalkınmayla ilişkisini kadın akademisyenler özelinde ele almaktadır.
Sürdürülebilir Kalkınma Hedefleri Bağlamında Kadın Akademisyenlerin Yaşam Boyu Öğrenme Deneyimleri
Keywords: Women's Studies; Kadın Araştırmaları